Work Sheet Development Based on Through Skills Based on High Level of Thematic Learning in 5th grade of Primary School (SD Negeri 040460 Berastagi T.A 2019/2020) - Serma Ulipa Simbolon; Khairil Ansari; Naeklan Simbolon (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
One of the demands of the 2013 curriculum is that learning must be integrated with the training of students' skills in higher-order thinking or HOTS. The ability of HOTS helps students not only know and understand a knowledge but is able to find the connectedness of information knowledge, involves the process of finding the concept of knowledge and applying knowledge to face a number of problems. The research was conducted at SD Negeri 040460 Berastagi in the odd semester of the 2019/2020 school year with theme 1: Animal and Human Motion Organs with sub theme 2: Human and Environment on Indonesian content. Based on the results of research and discussion, that the validity of the product seen from the design validator with the two validation system obtained very valid results with an average score of 84.61%. Likewise the results of the validators from the material experts who obtained an average score of 88.88 and were declared very valid with a two-time validation system. The conclusion of the linguist stated that the assessment of the design of LKPD language presentation based on high level thinking skills was in the very valid category with an average of 82.95%.